Customary Land as Mining Shares in the Perspective of Islamic Law - Salam, Safrin; Yahya, Safarudin; Jusu, La; Haniru, Rahmat; Khalil, Abdelmajid Idris Mohammed (Institut Agama Islam Negeri Kendari, 2026)
Customary land has a strategic position in the national legal system because it is a manifestation of the customary rights of customary law communities that are recognized and protected by the state. Modern economic developments, especially in the mining sector, have encouraged the emergence of legal innovations in the form of converting customary land into mining shares as a form of indigenous peoples' participation in economic activities. This study aims to analyze the legality and legitimacy of converting customary land into mining shares, specifically from the perspective of Islamic law. The research examines whether this practice aligns with Islamic principles of justice, benefit, and communal ownership, and how it can serve as an instrument for the economic empowerment of indigenous communities. The study employs normative legal methods, using legislative, conceptual, and comparative approaches to analyze primary and secondary legal materials. The results of the study show that the national legal system through the UUPA, the Mineral and Mineral Law, and the Limited Liability Company Law opens up space for the participation of indigenous peoples in the mining sector, but has not explicitly regulated the mechanism for converting customary land into shares. From the perspective of Islamic Law, this practice can be justified as long as it is based on the principles of justice (al-'adl), benefit (maṣlaḥah), and joint ownership (al-milkiyyah al-musytarakah), and is carried out through a transparent and equitable partnership model such as musharakah or mudharabah. Thus, the conversion of customary land into mining shares can be an instrument of economic empowerment of indigenous peoples that are legally valid and in accordance with Islamic values, as long as it guarantees collective rights, environmental sustainability, and sustainability of social benefits.